Meeting the 24‐hr movement guidelines: An update on US youth with autism spectrum disorder from the 2016 National Survey of Children's Health - Healy, Seán; Aigner, Carrie J.; Haegele, Justin A.; Patterson, Freda (Autism research, 2019)
The purpose of this study was to examine how adherence to the physical activity (PA), screen‐time (ST), and sleep duration guidelines differ between youth with autism spectrum disorder (ASD) and youth with typical development (TD). A secondary objective was to assess how PA, ST, and sleep duration varied among youth with ASD by age and ASD severity. Utilizing the 2016 National Survey of Children's Health data, parental reports of time spent by youth in PA, ST, and sleep were used to determine adherence to the 24‐hr movement guidelines for 1008 youth with ASD and 34 489 youth with TD. Multivariate logistic regression analyses determined that children with ASD were less likely to meet the guidelines for PA, ST, and sleep duration, and adolescents with ASD were less likely to meet the guidelines for PA and ST than participants with TD. Furthermore, logistic regression analyses determined adolescents with severe ASD to be less likely to meet the sleep guideline compared to adolescents with mild ASD. Overall, youth with ASD were significantly less likely to adhere to all three guidelines. The findings highlight the breadth of health behaviors that require intervention to counteract the poorer health status among youth with ASD. Autism Res 2019, 12: 941–951. © 2019 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary New health recommendations suggest children and adolescents should have at least 1 hr of physical activity, no more than 2 hr of screen‐time (e.g., television), and 9–11 hr of sleep (or 8–10 hr for children aged 14 or older) every day. This article looked at how children and adolescents with autism meet these new guidelines. The two main results were that: (a) children with autism were less likely to meet all three guidelines compared to children without autism, and (b) adolescents with autism were less likely to meet the guidelines for physical activity and screen‐time.